PERAN GURU AGAMA DAN BUDI PEKERTI DALAM MEMBANGUN SIKAP TOLERANSI MURID DI SMP NEGERI 3 GIANYAR - I Gede Purnama Arta; I Made Arsa Wiguna; Ida Ayu Adi Armini (Yayasan Pendidikan Literasi Borneo, 2026)
This descriptive qualitative study aims to analyze the actualization of the role of Religious and Moral Education teachers in transforming students' tolerance character at SMP Negeri 3 Gianyar. Data collection was conducted through moderate participant observation, in-depth interviews, and document analysis of all religious components within the school. The research results indicate that educators successfully integrated the five dimensions of multicultural education and internalized theological local wisdom applicably. The collective role-modeling strategy and the creation of equitable learning environments effectively shifted students' understanding from passive permissiveness to authentic appreciation of differences (respect). In conclusion, the adaptive social-personality competence of religious teachers serves as the primary moral anchor in bridging the ideal curriculum with sociological realities in multicultural educational institutions.